Biooxidation of a gold bearing arsenopyrite/pyrite concentrate - Miller, D M (Department of Chemical Engineering, 2016)
The objectives of this project have been to characterise the biooxidation of an auriferous pyrite/arsenopyrite flotation concentrate, and to interpret laboratory batch and continuous pilot plant data in the light of the logistic model. Furthermore, the possibility of predicting continuous biooxidation plant performance from batch data was considered. The batch testing was carried out on five narrowly sized fractions of Fairview concentrate, as well as on the bulk concentrate. Extents of removal of iron, arsenic and sulphide-sulphur were described by the logistic equation and values of the kinetic parameters obtained. Maximum rates of removal of these components, predicted by the logistic parameters, correlated well with experimentally determined rates of removal obtained from the linear portions of the fractional removal versus time curves. Bibliography: pages 93-98.